2013
DOI: 10.14334/jitv.v18i1.253
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sheep Stocking Density and Breed on Behaviour of Newly Regrouped Adult Rams

Abstract: Placing animals in cages with certain density and good grouping were two important aspects needed in intensive livestock production system to produce optimal production and animal welfare. The objective of this study was to examine effect of stocking density, breed and elapse of time on behaviour of newly regrouped, unacquainted adult rams from three sheep breeds i.e. Barbados Blackbelly Cross, Local Garut and Composite Garut, as possible factor causing variation in welfare status. Instantaneous scan sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However, interaction of day by breed was not significant for the examined parameters with the exception of vocalizations, indicating that the performance and behavioral traits were similarly affected in the Chios and Karagouniko ewes. In contrast, Engeldal et al [ 24 ] observed that rams of different breeds reacted differently to regrouping with respect to behavioral responses, reproductive performance and time needed for adaptation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, interaction of day by breed was not significant for the examined parameters with the exception of vocalizations, indicating that the performance and behavioral traits were similarly affected in the Chios and Karagouniko ewes. In contrast, Engeldal et al [ 24 ] observed that rams of different breeds reacted differently to regrouping with respect to behavioral responses, reproductive performance and time needed for adaptation.…”
Section: Discussionmentioning
confidence: 98%
“…Regrouping also resulted in short-term reduction of milk production and in lower protein and fat milk content. In another study, Engeldal et al [ 24 ] examined the behavioral reactions of rams of different breeds after regrouping. In all cases, agonistic behavior was the most commonly observed.…”
Section: Introductionmentioning
confidence: 99%